fAKTOR - FAKTOR YANG MEMPENGARUHI PRODUKSI CABAI KERITING(Annum Capsicum L) DI KECAMATAN JAYAPURA KABUPATEN OKU TIMUR (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2017)
This study was to analyze the Factors Affecting Production of Chili Curly in Jayapura District of Ogan Komering Ulu Timur.The research was conducted in the District Jayapura Ogan Komering Ulu Timur. Collecting data on the location of the research conducted in January through March - July 2017.The research method used survey method. The data collected consist of primary data and secondary data. Primary data were obtained from direct interviews with respondents using questionnaires (questionnaires) that have been prepared beforehand. Secondary data were obtained from the agency or agencies, such as the Central Bureau of Statistics OKU East, District Agriculture Office OKU Timur and UPTD Agriculture District Jayapura.Based on the research that has been done, it can be concluded that the significant factors (significant) towards the production of chilli curls is Land (X1), Manpower (X 2) Fertilizer ((X 4) and Pesticides (X 6).While the factors seeds (X 2) no real effect on the productivity of chilli curls in Jayapura District of Ogan Komering Ulu Timur.